(untitled) - Robert G Nunn (New York, 1997)
The book contains simple fundamental explanations of boiler room equipment operation, covering different types of systems - such as cooling towers, hot water boilers, and steam boilers - and their associated equipment. It includes helpful suggestions on how to cal culate amounts of chemical to be used in steam boilers, cooling towers, and ion exchange equipment. It also discusses scale, corrosion, algae growth, microbiological growth, and the chemicals and equipment used to control these problems. and it covers pumps, pump calculations, hydronic systems, control devices, and treatments
Keywords: feed-water purification,steam-boilers - water supply